PENGARUH BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN SERAPAN N, P DAN K JAGUNG PADA ABU VULKAN MERAPI - , BASYIT WULAN ISTIKAMAH, Prof. Dr. Ir. Azwar Maâas, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of the research was to study the of effect of peat and cow manure on growth and NPK uptake of corn (Zea mays L.) in volcanic ash Merapi. This research was done in green house, Soil Department, Faculty of Agriculture, Universitas Gadjah Mada. The experimental design used was factorial design with 2 factors. The first factor were organic matters (OM) consisting 7 levels: 0% of organic matter (K), 5% of peat (250g/5kg volcanic ash) (G1), 10% of peat (500g/5kg volcanic ash) (G2), 20% of peat (1000g/5kg volcanic ash) (G3), 5% cattle manure (250g/5kg volcanic ash) (K1), 10% of cattle manure (500g/5kg volcanic ash) (K2), 20% of cattle manure (1000g/5kg volcanic ash) (K3). The second faktor was the compsosition of fertilizer consisting two levels: petroganik (750kg/Ha) (P) and urea (400kg/Ha) (PU). Therefore, there were 14 treatments repeated 3 times so that the total treatments were 42 pots. The data were analyzed using ANOVA with 5% significance level and followed by DMRTâs test. Result of the research are cow manure 10% is produce the highest growth rate (40,40 cm/week), cow manure 20% produce the highest NPK uptake (N: 0,20 g/crop